Development of Tennis Achievements by Using Half the Competition - Maharani Fatima Gandasari; Ghana Firsta Yosika; Erna Yantiningsih; Muhammad Firman Annur (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Sports tennis is one of the sports that is included in 1 sports subject in the PKO study program. Where one of them is a tennis coaching course. In this semester, the field tennis event made a breakthrough in the form of a field tennis event within the PKO study program. The purpose of this service activity is to assist in making the 2023 PKO competition tennis championship event. This service activity consists of 3 stages including the preparation stage, the implementation stage and finally the evaluation stage. The results of implementing this competition tennis event consistently and continuously show an increase in tennis achievement for students of the PKO FKIP Study Program, Tanjungpura University.